Potential of row intercropping of potato and soy bean on incidences and severity of common pests and diseases of potato under the changing climatic environment in Malawi - Dambolachepa, H.B.; Phiri, A.T.; Mwenye, O.; Akinwale, G.; Longwe, K.; Vlugt, R. van der. (2023)
The potato production in Malawi is constrained however by a number of challenges among which increased pests’ pressure ranks the most pressing. The crop pests (insect pests, diseases, nematodes and weeds) interfere with potato growth and failure of crop to grow and produce by destruction of parts or of total crops. Field experiments were carried out aimed at investigating management options for potato for pests and diseases. The experiments were planted on research stations in the 2020/2021 cropping season at Chitedze, Bvumbwe, Makoka, Bembeke, Mbawa and Tsangano Agricultural Research Stations. There were 5 treatments laid in Randomized Complete Block Design (RCBD) replicated three times on station following a rotation system. Pure stands of the legumes and the intercrops were followed by a pure stand of potato in these subsequent years. Potato-soy bean intercrop followed 1:1, 2:1 and 3:1 alternate row. Pests and disease assessments were carried out on any pest/disease that was observed. Average disease severity scores were recorded in three phases thus, at seedling, vegetative and maturity. Plants from the net plot were scored individually using 0-9 disease scale while assessment of severity of insect pests was estimated using visual rating scale as per the 1-5 scale. Significant differences among the treatments were noted whereby low pests and disease severity scores were observed in 1:1 potato-soy bean intercrop. The present study demonstrated that potato-soy bean intercropping through 1:1 alternate row has potential role to suppress insect pests and diseases infestation and infection respectively and consequently, increase potato yields. It is recommended that farmers have to consider and use intercropping alongside induced resistances and biological control, as the environmentally safe alternative methods for pests and disease control.